Psychiatric Comorbidities in Children with Obesity - Pangestu, Randy (Scientia Psychiatrica, 2023)
Childhood obesity is a significant public health issue in the 21st century. Scientists have shown interest in studying the effects of childhood obesity on several aspects of health. Obesity comorbidities encompass more than just physical issues. The effects of juvenile obesity are far-reaching and include psychological comorbidities. The objective of this review was to specifically examine the psychiatric comorbidities that are linked to pediatric obesity. A comprehensive search was performed in PubMed to identify articles that provide information on the coexistence of pediatric obesity and other medical conditions. The pertinent data were retrieved and reviewed in a narrative manner. Research has shown that childhood obesity is linked to psychological comorbidities, including depression, reduced perceived health-related quality of life, emotional and behavioral issues, and lower self-esteem during childhood.